PROSES PENYUSUNAN ANGGARAN DAN PENILAIAN KINERJA DITINJAU DARI ASPEK PERILAKU (Studi Kasus Pada Perguruan Tinggi Swasta ”X” Di Surabaya) - Endang Dwi Retnani (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2009)
This study intends to find out the impact of planning and budgeting processes and performance measures on the behaviour of the responsibility center managers employed in a private university “X”. Method used in this study was qualitative research approach. The results showed that planning and budgeting submission processes with a bottom up participative approach influenced the behaviour of the responsibility center managers. Their appreciation and togetherness feeling was developed, as well as their commitment to execute the planned program and budgeting. Secondly, in the case that the approved planning and budgeting was implemented not as expected and planned without any explanation yielded a negative behaviour to the central managers that were shown by their less optimum potential works or with no action at all. Thirdly, financial performance measured with variant analysis was not reflecting the real performance of the responsibility center managers. The fact could cause misinterpretation of the management and also negative impact. It brought frustration among the responsibility center managers who actually had good performance. Furthermore, performance measurement, that is mainly based on financial aspects and neglecting non financial ones, influenced the reluctance of the responsibility center managers who just considered short term purposes and reluctant to make innovation. And last, by following steps suggested in the Balanced Scorecard, it could be able to define the Key Performanc Indicators of responsibility center managers with taking into consideration either financial or non financial aspects.